Application of the Laplace transformation for the analysis of viscoelastic composite laminates based on equivalent single-layer theories - Sy, Ngoc Nguyen; Lee, Jaehun; Cho, Maenghyo (International journal of aeronautical and space sciences, 2012)
In this study, the linear viscoelastic response of a rectangular laminated plate is investigated. The viscoelastic properties,expressed by two basic spring-dashpot models, that is Kelvin and Maxwell models, is assumed in the range to investigate the influence of viscoelastic coefficients to mechanical behavior. In the present study, viscoelastic responses are performed for two popular equivalent single-layered theories, such as the first-order shear deformation theory (FSDT) and third-order shear deformation theory (TSDT). Compliance and relaxation modulus of time-dependent viscoelastic behavior are approximately determined by Prony series. The constitutive equation for linear viscoelastic material as the Boltzmann superposition integral equation is simplified by the convolution theorem of Laplace transformation to avoid direct time integration as well as to improve both accuracy and computational efficiency. The viscoelastic responses of composite laminates in the real time domain are obtained by applying the inverse Laplace transformation. The numerical results of viscoelastic phenomena such as creep, cyclic creep and recovery creep are presented. KCI Citation Count: 11